Endoscopic Ultrasound Fine Needle Aspiration in the Diagnosis of Lymphoma. (28th March 2011) - Creemers, Koen; van der Heiden, Olaf; Los, Jan; van Esser, Joost; Newhall, David; Djamin, Remco S.; Aerts, Joachim G.
Abstract : In recent years, endoscopic ultrasound techniques with Fine Needle Aspiration (FNA) have become an increasingly used diagnostic aid in the differentiation of mediastinal lymphadenopathy. Endobronchial ultrasound (EBUS) and endoesophageal ultrasound (EUS) are now available for clinicians to reach mediastinal and paramediastinal masses using a minimally invasive approach. These techniques are an established component for diagnosing and staging lung cancer and their benefit in the diagnosis of lymphoma's has been highlighted in a number of case studies. However, the lack of tissue architecture obtained by cytological FNA specimens decreases the diagnostic accuracy for benign causes of thoracic lymphadenopathies, lymphomas, and histopathological subtyping of lung cancer. Accordingly, our study group have adapted the FNA sampling technique, resulting in tissue fragments that can be used for histopathological examinations. As an illustration, we report a case of follicular non-Hodgkin lymphoma, diagnosed on tissue fragments obtained by adjusted EUS FNA. We believe that this relatively simple adjustment to routine FNA sampling can help to overcome the diagnostic limitations inherent in cytology obtained by routine FNA.